Методи оцінки потенціалу підприємства - Харченко, В. В. (ХНУРЕ, 2025)
This work explores modern approaches to assessing enterprise potential, focusing on graph-analytical modeling and multi-criteria evaluation as key tools for strategic decision-making. The graph-analytical method, known as the «enterprise potential star», provides a structured visualization of key components, helping identify imbalances and areas for improvement. The multi-criteria evaluation method, based on utility theory and a goal-oriented approach, enables a comprehensive quantitative assessment of potential by considering multiple interrelated factors.
Keywords: оцінка потенціалу підприємства; потенціал підприємства